2015
DOI: 10.3126/ije.v4i2.12662
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production from renewable lignocellulosic biomass

Abstract: Effect of raw and biologically treated lignocellulosic biomass using cow dung slurry for biogas production is reported. Biomass is an energy source. Water containing biomass such as sewage sludge, cow dung slurry and lignocellulosic waste, has several important advantages and one of the key feature is renewability. Cow dung slurry has the potential to produce large amounts of biogas. Four categories of bacteria viz., hydrolytic, fermentative, fermentative acidogenic and acidogenic-methanogenic bacteria are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
3
0
0
Order By: Relevance
“…3). The yields of treatment B and C are in line with what [26] discovered in their research when groundnut shell was pretreated with size reduction. It was reported that treated groundnut shell yielded 200 ml biogas while untreated groundnut shell yielded 180 ml.…”
Section: Effect Of Size Reduction On Fresh Mass Biogas Yieldsupporting
confidence: 87%
See 2 more Smart Citations
“…3). The yields of treatment B and C are in line with what [26] discovered in their research when groundnut shell was pretreated with size reduction. It was reported that treated groundnut shell yielded 200 ml biogas while untreated groundnut shell yielded 180 ml.…”
Section: Effect Of Size Reduction On Fresh Mass Biogas Yieldsupporting
confidence: 87%
“…6) . Treatment B and C aligned with what [26] reported in their research. They reported that treated groundnut shell produced 64% methane while the untreated groundnut shell released 60% methane.…”
Section: Effect Of Size Reduction On Organic Dry Matter Methane Yieldsupporting
confidence: 85%
See 1 more Smart Citation